Development and assessment of the performance of a shared ventilatory system that uses clinically available components to individualize tidal volumes. - Hannon, David M.; Jones, Tim; Conolly, Jack; Judge, Conor; Iqbal, Talha; Shahzad, Atif; Madden, Michael; Kirrane, Frank; Conneely, Peter; Harte, Brian H.; O'Halloran, Martin; Laffey, John G. (BMC Anesthesiology, 2023)
Objectives: To develop and assess a system for shared ventilation using clinically available components to individualize tidal volumes. Design: Evaluation and in vitro validation study Setting: Ventilator shortage during the SARS-CoV-2 pandemic. Participants: The team consisted of physicians, bioengineers, computer programmers, and medical technology professionals. Methods: Using clinically available components, a system of ventilation consisting of two ventilatory limbs was assembled and connected to a ventilator. Monitors for each limb were developed using open-source software. Firstly, the effect of altering ventilator settings on tidal volumes delivered to each limb was determined. Secondly, the impact of altering the compliance and resistance of one limb on the tidal volumes delivered to both limbs was analysed. Experiments were repeated three times to determine system variability. Results: The system permitted accurate and reproducible titration of tidal volumes to each limb over a range of ventilator settings and simulated lung conditions. Alteration of ventilator inspiratory pressures, of respiratory rates, and I:E ratio resulted in very similar tidal volumes delivered to each limb. Alteration of compliance and resistance in one limb resulted in reproducible alterations in tidal volume to that test lung, with little change to tidal volumes in the other lung. All tidal volumes delivered were reproducible. Conclusions: We demonstrate the reliability of a shared ventilation system assembled using commonly available clinical components that allows titration of individual tidal volumes. This system may be useful as a strategy of last resort for Covid-19, or other mass casualty situations, where the need for ventilators exceeds supply.